The Use of Intact Fish Skin as a Novel Treatment Method for Deep Dermal Burns Following Enzymatic Debridement: A Retrospective Case-Control Study - Christoph Wallner; Jana Holtermann; Marius Drysch; Sonja Schmidt; Felix Reinkemeier; Johannes Maximilian Wagner; Mehran Dadras; Alexander Sogorski; Khosrow Siamak Houschyar; Mustafa Becerikli; Marcus Lehnhardt; Björn Behr (European Burn Journal, 2022)
Background: The optimal therapy for deep burn wounds is based on the early debridement of necrotic tissue followed by wound coverage to avoid a systemic inflammatory response and optimize scar-free healing. The outcomes are affected by available resources and underlying patient factors, which represent challenges in burn care and suboptimal outcomes. In this study, we aimed to determine optimal burn-wound management using enzymatic debridement (NexoBrid™, MediWound Germany GmbH, Rüsselsheim, Germany) and intact fish skin (Kerecis® Omega3 Wound, Isafjordur, Iceland). Methods: In this retrospective case series, 12 patients with superficial or deep dermal burn wounds were treated with enzymatic debridement followed by fish skin, Suprathel® (PolyMedics Innovations GmbH, Denkendorf, Germany), or a split-thickness skin graft (STSG). Patients’ outcomes regarding healing and scar quality were collected objectively and subjectively for 12 months after the burn injury. Results: Wounds treated with fish skin demonstrated accelerated wound healing, a significantly higher water-storage capacity, and better pain relief. Furthermore, improved functional and cosmetic outcomes, such as elasticity, skin thickness, and pigmentation, were demonstrated. The pain and itch expressed as POSAS scores (Patient and Observer Scar Assessment Scale) for fish skin decreased compared to those for wounds managed with an STSG or Suprathel. Importantly, fish skin-treated wounds had significantly improved sebum production and skin elasticity than those treated with Suprathel but showed no significant superiority compared to STSG-treated wounds. Conclusions: Enzymatic debridement in combination with intact fish skin grafts resulted in the faster healing of burn wounds and better functional and aesthetic outcomes than split-thickness skin grafts and Suprathel treatment.